An essential member of the HSP70 gene family of Saccharomyces cerevisiae is homologous to immunoglobulin heavy chain binding protein. - Nicholson, R C (1990)
Immunoglobulin heavy chain binding protein (BiP) is present in the lumen of the mammalian endoplasmic reticulum, where it associates transiently with a variety of newly synthesized secretory and membrane proteins or permanently with mutant proteins that are incorrectly folded. We describe a unique member of the Saccharomyces cerevisiae 70-kDa heat shock protein gene family (HSP70) that encodes a protein homologous to mammalian BiP. The DNA sequence contains a 2046-nucleotide open reading frame devoid of introns, and examination of the predicted amino acid sequence reveals features not found in most other yeast HSP70 proteins but which are present in BiP. Most notable are a 42-residue sequence at the N terminus that exhibits characteristics of a cleavable signal sequence and a C-terminal sequence, -His-Asp-Glu-Leu, that is involved in determining endoplasmic reticulum localization in yeast. The 5' flanking region of this gene contains two overlapping sequences between nucleotides -146 and -169 that closely resemble consensus heat shock elements. The yeast BiP gene is strongly heat shock-inducible, whereas the BiP genes in various other species are either weakly or non-heat-inducible. We demonstrate that a functional BiP gene is essential for vegetative growth. An evolutionary comparison of amino acid sequences of 34 HSP70 proteins from 17 species suggests that BiP genes share a common ancestor, which diverged from other HSP70 genes near the time when eukaryotes first appeared.